Invasion of the sausage snatchers - Cox, Michael; Smedley, Chris (Hodder Children's Books London, 2002)
The quiet, if dull, town of Chumley-by-Eck is the home of the blood sausage making industry. So it's the perfect place for blood-sucking vampires to begin their invasion ...Only eleven-year-old Claire Whimsy and her friend, Jason Turner, know what's going on. Can Claire and Jason stop the vampire invasion before it grips the world?